Social Capital Analysis as A Pattern of Developing Islamic Education an An Integral School Lukman Al-Hakim Surabaya - Saharuddin Saharuddin; Ulfiani Rahman; Moch. Mahmud; Syarifuddin Ondeng (Didaktika Religia, 2020)
This research seeks to uncover the strategy of development of work ethic and the spirit of learning of students at Islamic educational institutions at the Integral School of Lukman al-Hakim, Surabaya. The significance of this research lies in the thesis that concluded that as great as any renewal made by education, both public and Islamic, the conception of curriculum, concepts, management, methodologies, if not sustained by the spirit of the child Students to change, the change is futile. One of the students’ spirit analyses is social capital. It is proven in many quality education institutions with students who achievers apply the model of social capital development of students as the main gate. This research is an emperor who is approached by a qualitative approach to analysis. The data retrieval technique uses two methods; Documentation and observation. The researcher’s position in this regard as a participatory observer. After conducting the research, We found some final findings. Social capital analysis of students consists of social capital in community and social capital at school. Social Capital in the community consists of 1) genealogical Trust (belief in offspring), which is the assessment of society on the family of students and has a strong influence on the learning power of Students 2) Stimulation Trust (trust On stimulation). Social capital in this aspect is the optimism of parents and families to the students, 3) collaboration, meaning cooperation between students with families, with their fellow students, fellow learners but different levels and so on, and 4) values and norms. The last social capital of the community is concerned about the social norms that are so complex. Secondly, the social capital in the school consists of four things, namely mutual trust, networking, interaction or communication, value, and norms.